Vegetable cultivation in Eastern Nepal: resource use efficiency and socio-economic drivers of adoption - Sagar Ghimire; Rishi Ram Kattel (Cogent Food & Agriculture)
Resource use efficiency and socioeconomic factors influencing the adoption of vegetables for cultivation were analyzed using cross-sectional data from randomly selected 120 vegetable producers in the Udyapur District of eastern Nepal. A field survey was conducted between October and November 2019. Five major vegetables of the district based on the area of cultivation, namely potato, cauliflower, radish, cabbage, and tomato, were taken for the study. The benefit-cost ratio was highest for cauliflower (2.46), followed by tomato (2.20), radish (2.01), cabbage (1.70), and potato (1.36). The Cobb-Douglas production function revealed that the cost of human labor and the cost of manure and fertilizer had a significant positive impact on income from vegetables, whereas the cost of seed had a significant negative impact on income from vegetables. The resource use efficiency analysis shows that the costs incurred for human labor, tillage, seed, irrigation, and packaging/marketing were overused. In contrast, the costs of manure and fertilizer are underused. The Logit model was used to study various factors affecting the adoption of vegetables for cultivation in the study area, which revealed the relationship and extent of the impact of various socio-economic factors on the adoption of the five different vegetables.